PENGEMBANGAN MEDIA BIG BOBATAR BERBASIS SAINTIFIK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN TAMBAKAJI 01 KOTA SEMARANG - An Nisaa' Novitaningtyas; Elok Fariha Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The subpar achievement in mathematics learning and the underutilization of learning resources in the fourth grade at SDN Tambakaji 01 Semarang City are the driving forces behind this research. The purpose of this research was to develop, test the feasibility, and effectiveness of scientific-based Big Bobatar media on the mathematics learning outcomes of fourth-grade students on the area material. This research method is RnD which refers to the ADDIE paradigm. The development of scientific-based Big Bobatar media was considered feasible to use based on 81.67% validation results from material experts and 91.67% from media experts. The results effectiveness of Big Bobatar media on increasing the totality of pretest-posttest learning outcomes through the t-test obtained a t count of 34.241> t table 2.060 then the results of the average increase test (N-gain) of 0.73 and included high criteria. Thus, the use of scientific-based Big Bobatar media is effective and useful in mathematics learning for fourth-grade area material.